Intelligence Collaboration as a Potential Mitigation of the Golden Visa Threat - Rakha Candra Permana; Margaretha Hanita; Andry Indrady (Journal of Social Research, 2023)
The Golden Visa policy, aimed at attracting quality investors and global talents, has gained prominence globally, including in Indonesia through Permenkumham 22 of 2023. This policy is designed to enhance the domestic economy by offering incentives and streamlined processes for foreign investors and talents. However, the potential threat posed by the Golden Visa system is a subject of concern, prompting this research to delve into its implications using qualitative research methods and an inductive approach. The analysis reveals that the potential threat of the Golden Visa lies in its capacity to negatively impact national security. Recognizing the significant role of the Directorate General of Immigration, the agency vested with authority in the immigration sector, becomes crucial in mitigating these threats. The integration of intelligence analysis and collaborative governance within the Directorate General of Immigration can serve as an effective early detection mechanism for potential threats associated with the Golden Visa program. In conclusion, while the Golden Visa policy holds the promise of economic benefits for Indonesia, it is imperative to address and manage the potential security threats it may pose. By leveraging the expertise of immigration authorities and employing strategic intelligence analysis, Indonesia can strike a balance between attracting foreign investments and talents while safeguarding its national security interests.